Promoting strategic internal communication in governance to enhance employee creativity in organization - Nur Hidayah, Shamsul Azhar; Fadzida, Ismail; Noor Akma, Abu Bakar (Penerbit Universiti Malaysia Pahang, 2024)
The global construction sector still lacks a full understanding of the significance of communication, resulting in weaknesses in the business process. This principle applies to the building industry as well, as communication breakdowns often lead to financial losses due to unrecognized risks. The objective of this research is to investigate the correlation between organizational communication and the generation of creativity within the organizational governance. The study analyzed 134 questionnaire data gathered from Ipoh, Perak, using the partial least squares structural equation modelling (PLS-SEM) approach. The results indicate that when internal communication and leadership communication in governance are symmetrical, individuals are more likely to receive feedback from a variety of interpersonal sources, including supervisors, colleagues, and peers from different departments. This enhances creativity. The study concludes that communication leadership at the supervisory and senior levels positively impacts the symmetrical system's internal communication, leading to an increase in novel ideas within the organization.